2020
DOI: 10.1182/bloodadvances.2020002308
|View full text |Cite
|
Sign up to set email alerts
|

Targeted FGFR inhibition results in a durable remission in an FGFR1-driven myeloid neoplasm with eosinophilia

Abstract: Key Points A novel PCM1-FGFR1 gene rearrangement was identified in a patient with a myeloid neoplasm with eosinophilia. Futibatinib, an oral selective small molecule inhibitor of FGFR1-4, resulted in a durable complete hematologic and cytogenetic remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Significant amount of this receptor is expressed on the plasma membrane of three different t(4;11) leukemia cell lines, i.e., RS4;11, MV4-11, and SEM ( Figure 1 A). FGFRs are involved in multiple myeloma, in myeloproliferative disorder, and, importantly, in B-cell precursor (BCP) ALL, the latter including the MLL-rearranged leukemias, thereby supporting their crucial role in hematologic malignancies [ 40 , 41 , 42 ]. Interestingly, FGFR signaling can contribute to prednisolone resistance in BCP ALL cells; however, as activating mutations in this RTK family are very rare, information concerning their role in ALL is limited [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant amount of this receptor is expressed on the plasma membrane of three different t(4;11) leukemia cell lines, i.e., RS4;11, MV4-11, and SEM ( Figure 1 A). FGFRs are involved in multiple myeloma, in myeloproliferative disorder, and, importantly, in B-cell precursor (BCP) ALL, the latter including the MLL-rearranged leukemias, thereby supporting their crucial role in hematologic malignancies [ 40 , 41 , 42 ]. Interestingly, FGFR signaling can contribute to prednisolone resistance in BCP ALL cells; however, as activating mutations in this RTK family are very rare, information concerning their role in ALL is limited [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The next generation of more specific drugs, largely only targeting the FGFR family, included ponatinib, which was originally developed to target the mutant BCR-ABL rearrangement in CML [46] but showed a reasonable specificity for FGFR1 at lower concentrations. In one case, after showing chemotherapy resistance, partial remission was achieved using ponatinib [32] , although other studies suggested it was less effective [6] . Recently more successful remission was achieved using pemigatinib on a single patient with a t(8;9) rearrangement, although the patient died of unrelated complications [7] .…”
Section: Treatment Of Mln-eo Fgfr1mentioning
confidence: 96%
“…As a result, our understanding of its pathobiology has been limited and conducting clinical trials has been challenging. Consequently, the majority of case reports describe only a single patient with limited molecular analysis and, where drug treatments were reported only single cases were involved [ 7 , 22 , 31 33 ] . To overcome these limitations, several groups have developed murine models of the disease to study the genetic changes responsible for transformation of the hematopoietic stem cell and to investigate the use of molecularly targeted therapies in suppressing the disease without the limitations of incidence and variable diagnosis imposed in human populations.…”
Section: Clinical Analysismentioning
confidence: 99%
See 2 more Smart Citations